POETRY TEACHING MATERIAL DESIGN FOR ELEMENTARY SCHOOL - Marlina Eliyanti Simbolon; Hamdan Hamdan (Indonesian Journal of Elementary Teachers Education, 2020)
This research explains about the Design of Poetry Teaching (Qualitative Descriptive Research Against Poetry Appreciation Class V SD Negeri 3 Awirarangan). The formulation of the problems is: (a) How to appreciate poetry class V student SD Negeri 3 Awirarangan, (b) How to analyze Basic Competence. 3.3 Reading poetry with appropriate pronunciation and intonation, (c) How to design poetry teaching based on students' poetry appreciation and analysis of Basic Competencies 3.3. The method used is descriptive qualitative. Data collection techniques are observation, interview, literature study, documentation, and argumentative. Data processing techniques are analysis and design. The object of research is the poetry teaching of class V. The conclusion of the research results are based on the: (1) results of observation, interview and collected questionnaires, poetry appreciation of class V students of SD Negeri 3 Awirarangan is at low appreciation stage; 2) result of the analysis of KD 3.3 produces the subject of class V poetry teaching including the meaning of poetry, the intrinsic element of poetry, and the things that are considered in the poetry (pause, pressure, pronunciation and intonation); 3) design of a one-of-a-month drama script is divided into 5 scenes each having sub scenes, the drama consists of 10 characters (teacher, late student, student 1-8) of the drama script developed based on the selected theme of education.Keywords: poetry appreciation; teaching material; drama script.